Resourcing Salta. Viticulture, soy farming and the contested commodification of land - Hafner, Robert; Rainer, Gerhard (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
In recent years, the increased significance and internationalisation of land tenancy and purchase has led to intensive scientific discussions. In so doing, a majority of the studies try to draw conclusions of the extent and relevance of the land rush by analysing macro-economic data and structures. In our paper, we extend this analysis by applying an ethnographic, local-regional perspective. Argentina has experienced a strong neo-liberal phase in the 1990s; modernisation and particularly globalisation of agriculture has played a central role. The intensification of land use was coupled with new actor constellations, whereby land ownership and tenancy structures changed fundamentally. Embedded in this national context we contrast two production peripheries in the province of Salta: viticulture in the Andean Calchaquí Valleys and soy farming in the Chaco lowlands. In the context of the Chaco’s soy production the agrarian restructuring goes along with the appearance of actors fol-lowing a short-term logic of capital accumulation (almost exclusively through tenancy-relationships). More often than not, so-called pooles de siembra (driven by financial capital) or national agro-actors use the Chaco Salteño as expansion territory and for risk diversification, fostering monofunctional land use. In contrast, actors of wine business in the Calchaquí Valleys follow predominantly long-term logics: Via land purchase and high-level investments in cultivation and irrigation quality wines are produced for a national and international niche market. Due to the association of wine with amenity quality and social status, a tourism and real estate boom has emerged, whereby the storing of and speculation with (surplus) capital is a crucial factor. Land becomes an attractive capital investment due to massively rising prices. The goal of our paper is to analyse and contrast land use changes in the respective study areas and, by doing so, we aim to contribute to the ongoing discussion on the current land rush/land grabbing in Latin America.